Brain Ways: Meynert, Bachelard and the Material Imagination of the Inner Life. Issue 3 (13th June 2016) - Phelps, Scott
Abstract : The Austrian psychiatrist Theodor Meynert's anatomical theories of the brain and nerves are laden with metaphorical imagery, ranging from the colonies of empire to the tentacles of jellyfish. This paper analyses among Meynert's earliest works a different set of less obvious metaphors, namely, the fibres, threads, branches and paths used to elaborate the brain's interior. I argue that these metaphors of material, or what the philosopher Gaston Bachelard called 'material images', helped Meynert not only to imaginatively extend the tracts of fibrous tissue inside the brain but to insinuate their function as pathways co-extensive with the mind. Above all, with reference to Bachelard's study of the material imagination, I argue that Meynert helped entrench the historical intuition that the mind, whatever it was, consisted of some interiority – one which came to be increasingly articulated through the fibrous confines of the brain.